Substantial justice : an anthropology of village courts in Papua New Guinea - Goddard, Michael (Michael Bruce) (Berghahn Books, 2009)
"Papua New Guinea's village court system was introduced in 1974, partly in an effort to overcome the legal, geographical, and social distance between village societies and the country's formal courts. There are now more than 1100 village courts all over PNG, hearing thousands of cases each week. This anthropological study is grounded in ethnographic research on three different village courts and the communities they serve. It also explores the colonial historical background of the establishment of the village court system, and the local and global processes influencing the efforts of village courts to deal with everyday disputes among grassroots Melanesians."